DEVELOPING MEDIA BY USING PODCAST IN TEACHING LISTENING OF RECOUNT TEXT TO GRADE X STUDENTS OF TOURISM VOCATIONAL SCHOOL - Theofani Elisabeth Situmorang; Indra Hartoyo (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2021)
DEVELOPING MEDIA BY USING PODCAST IN TEACHING LISTENING OF RECOUNT TEXT TO GRADE X STUDENTS OF TOURISM VOCATIONAL SCHOOL *Theofani Elisabeth Situmorang **Indra Hartoyo ABSTRACT Situmorang, Theofani Elisabeth. Registration Number: 2163121044. Developing Media By Using Podcast in Teaching Listening of Recount Text to Grade X Students of Tourism Vocational School. A Thesis. English Educational Program. State University of Medan.2020. The study was aimed to develop media by using Podcast in teaching Listening of Recount text to grade X students of Tourism Vocational School. This study was conducted by using Research and Development (R&D) design through six stages: gathering the data, need analysis, design media, validating by experts, revising, and final project. The subject of the study was Grade X Students of Tourism Vocational School. The instruments of data collection were gathered by administrating interview and distributing questionnaire to 28 respondents to get students’ needs. The interview and questionnaire result proved that the students need English learning media which can motivate students to understand listening recount text. The product was validated by two experts; English lecturer and English teacher. The product result was Podcast that contains audio media to be used in mastering the recount text listening. The result of experts’ validation showed that the media was an appropriate media to be used in teaching listening recount text by getting average percentage of 97.5% categorized as excellent. Keywords: Podcast, Recount Text, Research an(R&D)